Does Industry Type Moderate the Relationship between Energy Efficiency and Financial Performance of Firms Listed on the Johannesburg Stock Exchange? Array - Dzomonda, Obey (Acta Universitatis Danubius. Œconomica, 2021)
Objectives: The current study investigated the effect of energy efficiency on financial performance using industry type as a moderating variable. Prior Work: It has been discovered that there is an inconclusiveness of findings in existing literature regarding the link between energy efficiency and financial performance. Approach: The study adopted a quantitate research method using secondary data. Panel data was collected for 8 years from 16 firms listed on the FTSE/JSE. The panel regression model was used to run the panel data. Specifically, the Feasible Generalized Least Squares was used, Results: The findings showed that attaining energy efficiency significantly and negatively influence financial performance (EPS) of the firms considered in this study. Interestingly, the link between energy efficiency and financial performance (EPS) improved from negative to positive when the moderation effect of industry type was introduced. Implications: Practically, the findings of this study should assist managers of listed companies to invest in energy efficiency initiatives beyond just compliance but as a strategy to enhance operational efficiency and drive positive financial performance. Value: The novelty of this study is that it further tested the moderating effect of industry type on the energy efficiency and financial performance nexus which generated new empirical findings which were lacking in South Africa.